Probing optical excitations in chevron-like armchair graphene nanoribbons. Issue 46 (16th November 2017) - Denk, Richard; Lodi-Rizzini, Alberto; Wang, Shudong; Hohage, Michael; Zeppenfeld, Peter; Cai, Jinming; Fasel, Roman; Ruffieux, Pascal; Berger, Reinhard Franz Josef; Chen, Zongping; Narita, Akimitsu; Feng, Xinliang; et al.
Abstract : RDS, HREELS and theory to probe optical excitations and catch GNRs in the act of their formation. Abstract : The bottom-up fabrication of graphene nanoribbons (GNRs) has opened new opportunities to specifically tune their electronic and optical properties by precisely controlling their atomic structure. Here, we address excitation in GNRs with periodic structural wiggles, the so-called chevron GNRs. Based on reflectance difference and high-resolution electron energy loss spectroscopies together with ab initio simulations, we demonstrate that their excited-state properties are of excitonic nature. The spectral fingerprints corresponding to different reaction stages in their bottom-up fabrication are also unequivocally identified, allowing us to follow the exciton build-up from the starting monomer precursor to the final GNR structure.